Pengaruh Perputaran Modal Kerja, Operating Leverage dan Financial Leverage terhadap Profitabilitas Perusahaan Sektor Retail di Bursa Efek Indonesia - Muhammad Fuad; Oyami Sara; Muhammad Nur Daud (Universitas Medan Area, 2019)
This study aims to analyze the influence of working capital turnover, operating leverage and financial leverage on profitability. The research object is thirteen retail sector companies listed on the Indonesia Stock Exchange (IDX) which are selected based on certain criteria. Secondary data are in the form of financial statements from each company in the period 2013 to 2017, and analyzed using multiple linear regression methods. The results obtained state that each working capital turnover, operating leverage and financial leverage have a positive influence on the profitability of retail sector companies on the IDX. However, the results of the partial test prove that only financial leverage has a significant influence on profitability; while working capital turnover and operating leverage proved to be insignificant. Simultaneously, the three independent variables analyzed have a significant influence on the profitability of retail sector companies on the IDX.